Dominance of the Batu City Tourism Sector by Jatim Park Group - Jihan Putri Rahmadi; Farhan Hakim Pratama; Sindhuaji Darmawan; Amanda Putri Prasetya; Prisca Kiki Wulandari (Cv. Kayaswara, Indonesia, 2025)
Tourism development in Batu City has shown rapid growth over the past decade, largely driven by private investment from the Jatim Park Group (JTPG). This study aims to analyze the impact of JTPG’s dominance in the tourism sector and the patterns of collaboration within Batu City's tourism governance network, particularly in the context of private corporate dominance. Employing a qualitative approach, data were collected through in-depth interviews, observations, and analysis of government documents and private publications. The findings reveal that JTPG's dominant role influences not only destination management but also spatial planning policies and the distribution of local economic benefits. Collaboration between the government, communities, and businesses tends to be symbolic and imbalanced, with limited facilitation from the government as a collaborative leader. These findings highlight the need to strengthen the institutional capacity of the government and reposition the role of the community to ensure a more inclusive and sustainable tourism development. In conclusion, JTPG’s dominance creates a form of structural dependency that threatens actor diversity in tourism governance and undermines regional autonomy.